Comfortable Room as a Media for Implementation of Case Study Events for Students of the Faculty of Communication Sciences and the Faculty of Engineering, Mpu Tantular University Jakarta Real Work Lectures in 2022, Mpu Tantular University Jakarta Cipinang Besar Utara Village, Jatinegara District, East Jakarta City, DKI Jakarta Province - Edison Hotaguan Manurung; Sri Prasetyo Widodo; Witardi G; Morhan Aser Sirait; Mochamad Azis Prasetya; Alfan Dolly Eben Hasudungan; Nida Isnaini; Linda Maruah Azizah; Lusius Ripaldi Sihombing; M Khasbi Assiddiki (Indonesian Journal of Advanced Social Works, 2023)
In an event, the room is one of the things that must be considered. An event can be said to be good if the placement and arrangement of furniture and other equipment as well as reading materials need to be placed and arranged in such a way that what is presented looks attractive. Through the KKN program carried out by students at Mpu Tantular University Jakarta with the dedication method by renovating campus facilities which is expected to trigger other parties to concentrate more on determining the room for holding the event.